Cognition, mental health, and quality of life in patients with chronic and episodic migraine during the interictal period - Diana Carolina López-Medina; Alejandra Arboleda-Ramírez; Sara Ríos-Díaz; Renato Zambrano-Cruz; Andrés Arboleda-Jaramillo; Cristian Betancur-Henao; Marcela Henao-Pérez (BMC Neurology)
Abstract Introduction Migraine is a highly prevalent and disabling condition, not only due to its painful symptoms but also because of its significant impact on mental health and cognitive functioning, leading to a considerable deterioration in quality of life. This study aimed to evaluate the cognitive profile, mental health, and quality of life in patients with chronic and episodic migraine during the interictal period, and to explore their relationship with sociodemographic and clinical variables. Method This observational, descriptive, cross-sectional analytical study included 60 patients diagnosed with chronic or episodic migraine, who were enrolled in a health program for headache patients between 2010 and 2016. Cognitive function, anxiety and/or depression symptoms, and quality of life during the interictal period were assessed. Descriptive analyses were conducted, and associations were evaluated by configuring primary (type of migraine) and alternative events (cognitive impairment, depression and/or anxiety, and poor quality of life). Results The mean age of the participants was 45 years (SD ± 8), with 83.3% being women and 93.3% belonging to middle and low socioeconomic strata. Of the 60 patients, 83.3% (50) were diagnosed with chronic migraine, while the remaining had episodic migraine. The use of one or more cognition-altering medications was observed in 90% of patients with chronic migraine and 60% of those with episodic migraine (p = 0.02). Anxiety was more prevalent in patients with episodic migraine, whereas depression was more common among those with chronic migraine. Female gender, middle socioeconomic status, and longer disease duration were significantly associated with chronic migraine. Among the 57 patients who completed the Mini-Mental State Examination, 38.6% had cognitive impairment, which decreased with longer migraine duration and better social interaction. Memory and selective attention were the most affected cognitive domains in both groups. No significant associations were found for the other variables after adjusting for confounders. Conclusions Chronic migraine significantly impacts mental health, cognition, and quality of life, with depression and cognitive impairments being prevalent. Social interaction and longer disease duration may protect against cognitive decline, highlighting the need for multidisciplinary, personalized interventions addressing neurological and psychosocial challenges.